2018
DOI: 10.1038/s41385-018-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary antigen encounter regulates the establishment of tissue-resident CD8 memory T cells in the lung airways and parenchyma

Abstract: Resident memory CD8 T (TRM) cells in the lung parenchyma (LP) and airways provide heterologous protection against influenza virus challenge. However, scant knowledge exists regarding factors necessary to establish and maintain lung CD8 TRM. Here we demonstrate that, in contrast to mechanisms described for other tissues, airway and LP CD8 TRM establishment requires cognate antigen recognition in the lung. Systemic effector CD8 T cells could be transiently pulled into the lung in response to localized inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 32 publications
11
143
0
1
Order By: Relevance
“…Previous studies have shown that the maintenance of Trm T cells within lung niches is influenced by the presence and longevity of antigen depots (18,21,23). Following IAV-nanovax vaccination, we observed the presence of both CD4 and CD8 Trm cells within the lungs on day 32 and 45 post vaccination at numbers similar to those observed in an IAV infected lung (Figure 4).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have shown that the maintenance of Trm T cells within lung niches is influenced by the presence and longevity of antigen depots (18,21,23). Following IAV-nanovax vaccination, we observed the presence of both CD4 and CD8 Trm cells within the lungs on day 32 and 45 post vaccination at numbers similar to those observed in an IAV infected lung (Figure 4).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, studies in animal models of IAV infection have demonstrated that the pulmonary immune system imprints effector T cells with lung homing capabilities as well as induces the formation of local tissue-resident memory T and B cells that are thought to provide optimal protection (13)(14)(15)(16)(17)(18). This tissue-resident phenotype is thought to depend on antigen longevity, antigen presenting cells (APC), and tertiary structures within the tissues (18)(19)(20)(21)(22)(23). Therefore, vaccines that utilize tissue-specific factors and pathways critical for the induction of pulmonary T and B cell responses to generate local as well as systemic immunity by mimicking IAV infection would be predicted to confer more robust protection.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in CXCR6 expression between resident and vascular cells, and between CD69 + and CD69 − resident cells, suggested that antigen encounter in the lung environment may be important for maintaining CXCR6 expression. To determine if pulmonary antigen exposure was necessary for CXCR6 up-regulation, we used a method to establish systemic effector T cells and "pull" them to the lungs (McMaster et al, 2018). Mice were i.m.…”
Section: Cxcr6 Is Expressed On Mouse and Human Lung-resident (Lung Rementioning
confidence: 99%
“…One of these first studies by Christensen et al that investigated airway memory T cells found that a single intraperitoneal priming regimen was inferior to an intraperitoneal-prime and intranasal-boost regimen for protection against a heterosubtypic influenza challenge (8). Although this defect was originally attributed to differences in the number of circulating influenza-specific memory CD8 T cells between vaccination regimens, armed with current knowledge it is likely that the lack of influenza-specific memory CD8 T cells in the respiratory tract after intraperitoneal priming was also a major contributing factor (35,41,47). Another early study provided the first evidence of a CD69 + ''resting'' influenza-specific memory CD8 T cell population in the airways that was highly prevalent on day 50 postinfection, but gradually disappeared over the next 3-4 months (30).…”
Section: Memory Cd8 T Cellsmentioning
confidence: 99%
“…However, unlike T RM in other sites, the requirements for establishment of T RM in the lung, and the longevity of these cells in the tissue, are unique. Several reports have shown the generation of lung T RM requires that activated effector T cells re-encounter their specific antigen in the lung tissue (35,41,47). This has important implications for vaccination strategies, as intramuscular (i.m.)…”
Section: Memory Cd8 T Cellsmentioning
confidence: 99%